Pioderma gangrenoso e artrite reumatóide: relato de caso Pyoderma gangrenosum and rheumatoid arthritis: case report - Izelda Maria Carvalho Costa; Lucas Souza-Carmo Nogueira (Sociedade Brasileira de Dermatologia, 2005)
É descrito caso de paciente de 15 anos que apresenta várias lesões de pioderma gangrenoso 16 meses antes de iniciar acometimento por artrite reumatóide e com excelente resposta à terapêutica com clofazimina. The case is described of a 15-year-old patient that presented several pyoderma gangrenosum lesions 16 months before onset of rheumatoid arthritis manifestations. There was an excellent response to therapeutics using clofazimine.